Bridging Policy and Practice: An Analysis of Outcome-Based Education (OBE) Curriculum Implementation Using David C. Korten’s Fit Model - Wike; Novita, Evi Diyah; Haryono, Bambang Santoso (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the implementation of the Outcome-Based Education (OBE) curriculum at a faculty in a state-owned university in East Java using David C. Korten’s fit model, which emphasizes three elements: program, organization, and beneficiary alignment. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with 12 lecturers, 6 students, and 3 administrative staff members, as well as through observations and documentation studies. The data were analyzed using the interactive analysis model. The results indicate that the implementation of OBE has achieved a progressive alignment between program design, organizational capacity, and beneficiaries, although it remains in a consolidation phase. The adoption of the Case Method and Project-Based Learning, supported by the SIM OBE information system, has successfully shifted the academic culture toward a student-centered learning approach, with average learning outcome achievements exceeding 70 percent of the class average score. The discussion of the findings suggests that while structural support and stakeholder involvement are relatively strong, several challenges remain, particularly regarding the consistency of pedagogical practices and the standardization of assessment among faculty members. These dynamics indicate that successful curriculum transformation requires a “triple alignment” among policy regulations, organizational culture, and classroom-level implementation. This study contributes to the conceptual framework of educational policy implementation by emphasizing that academic transformation is not merely administrative but requires strong synergy between curriculum design and operational capacity. The findings provide strategic insights for higher education institutions to optimize OBE implementation through the systematic integration of digital systems, faculty mentoring, and stakeholder collaboration to enhance graduate competitiveness.